OFERTAS E MODOS DE APROPRIAÇÃO DOS COMENTÁRIOS DOS LEITORES NOS JORNAIS DIÁRIO DOS CAMPOS E GAZETA DO POVO - Santos, Luciane Justus dos (2015)
Understanding the appropriations process interactions from readers in newspapers and how these counterflow impact the news of the construction process is the objective of this study. It is considered the interface between the print platform and online journalism feature printed on the twenty-first century, and the focus is on interaction materialized based on their action via comments on the direction of the newspaper deals - what is published daily. Empirical research carried out in the newspapers dos Campos and Gazeta do Povo, gathers empirical data that make up the analysis. That is, it is a look at the offers (opinions) of players, the management and appropriations that the newspaper realizes from them. Through systematic observations have been identified elements that enable and / or determine the intensity and the way the newspaper perceives and appropriates the offers generated in the communication process from the perspective of consumption and circulation. This perspective offers a position to identify the flows and counterflow, tensions between production and reception systems. In this case, analyzing the strategies and protocols that both develop or establish to establish their exchanges and produce their speeches. The elements in the process of appropriation of the offers and considered for the analysis are the available interest channels, filters and the selection process / editing of comments and how they are again offered for consumption (reframed). The study considers the issue of new ambiences of discursive circulation while widen participation and promote new circuits that the productive system, in turn, does not account for control with traditional constituents protocols of their reading contracts. Importantly, not carried out a study on the content of news or comments, but the structure and protocols that enable the circulation of the "opinion of readers." Reflection on the subject is grounded in the theoretical contributions of gatekeeping and the theory of enunciation problematized with the specifics of journalistic practice.